Estudio hematológico de bovinos criollos y Brown Swiss criados en los Andes de Perú - Gonzales Aparicio, Gonzalo W. (2020)
The basic hematological characteristics of a group of 184 Creole cattle (CRIZA) and 128 Brown Swiss cattle (BSZA) both male and females, reared in the Andes of Peru between 3213 and 4309 meters above sea level, were evaluated and compared with samples from a group of 11 cattle with brisket disease (BSMA) and with another group of 31 Brown Swiss cattle reared between 243 and 1306 meters above sea level (BSZB). The red blood cell count (RBC) was 14.95, 8.34, 8.25 and 7.10x106/μl in BSMA, BSZA, CRIZA and BSZB, respectively. Haematocrit (Ht) was 61.44, 45.83, 42.61 and 34.99% for BSMA, CRIZA, BSZA and BSZB, respectively. Haemoglobin (Hb) was 16.26, 12.86, 12.22 and 9.65 g/dl in BSMA, CRIZA, BSZA and BSZB, respectively. The averages showed wide variation. Taking the Ht criterion, BSZA and CRIZA cattle belonging to the upper decile were identified, forming two groups with extreme values (BSZAVE and CRIZAVE), which presented values of Ht, RBC and white blood cell count (WBC) lower than those of BSMA cattle (p<0.01). An overall correlation of 0.92 was found between Hb and Ht, the same that ranged from 0.83 in BSMA to 0.94 in BSZB (p<0.05), but without significant difference between BSZA and CRIZA. High values of Ht, RBC and WBC could be considered as indicators related to the susceptibility of cattle to hypoxic conditions due to altitude.